Identification, cloning and functional characterization of novel sperm associated antigen 11 (SPAG11) isoforms in the rat - Yenugu, Suresh (BioMed Central, 2006)
BACKGROUND: Sperm binding proteins and their C-terminal peptides of the Sperm Associated Antigen 11 (SPAG11) family were found to play an important role in epididymal innate immunity in addition to their role in sperm maturation. However, the expression of Spag11 transcripts in rodents is not well documented. METHODS: Computational analysis was employed to identify novel Spag11 isoforms in the rat. RT-PCR analyses were carried out on RNAs isolated from the male reproductive tract tissues of rat using gene specific primers for Spag11c and Spag11t. The identities of PCR products were confirmed by sequencing. Tissue distribution, developmental expression and androgen regulation of Spag11t and Spag11c were studied using RT-PCR. The antimicrobial activities of recombinant Spag11t and Spag11c were tested against E coli in a colony forming unit assay. RESULTS: In this study, we identified two novel Spag11 transcripts, namely, Spag11t and Spag11c derived from the long arm of chromosome 16 in the rat (Rattus norvegicus), using both in silico and molecular biology approaches. Spag11c is expressed in all three regions of the epididymis, in testis and in ovary but is absent from the seminal vesicle. Spag11t expression is confined to the caput and it is not expressed in the testis, seminal vesicle or ovary. Age dependent expression of Spag11t and Spag11c was observed in the epididymides of rats (10–60 day old). Their expression was found to be most abundant in the adult rat (60 day) suggesting roles in mature reproductive function. Further, both Spag11t and Spag11c expression was down regulated in castrated rat epididymides and the expression was maintained in the testosterone replaced castrated rats. SPAG11C is a potent antibacterial agent. SPAG11T also displayed bactericidal capacity although weaker than SPAG11C and SPAG11E. CONCLUSION: The abundant expression of Spag11t and Spag11c in the male reproductive tract suggests an important role in male reproductive tract immunity. Their expression is developmentally regulated and androgen dependent. Characterization of novel SPAG11 isoforms will contribute to our understanding of the role of epididymal proteins in sperm maturation and innate immunity.